CONTROL OF THE PROPERTIES OF TRANSPARENT CONDUCTING OXIDES DEPENDING ON THE SOLUTION PARAMETERS - T.O. Zinchenko (Penza State University Publishing House, 2021)
Background. Traditional methods of synthesis of transparent conducting oxides-a promising material for opto-and semiconductor devices and devices-have serious disadvantages due to the use of vacuum and high production costs. The aim of the work is to study the effect of the solution parameters on the properties of transparent conducting oxides when using the spray-pyrolysis method, which eliminates these disadvantages. Materials and methods. As a material for the production of transparent conducting oxides, tin oxide doped with antimony is selected, which has the following advantages:chemical inertia, stability at high temperatures and in atmospheric conditions, sufficiently high transparency and conductivity. The coating was synthesized by spray pyrolysis, which eliminates the disadvantages of other methods that require a vacuum, and therefore have a high production cost. Results. The influence of the solution volume, impurity concentration, and precursor concentration on the properties of transparent conductive coatings (surface resistance, specific conductivity, carrier concentration, and free path length) is studied. Conclusions. As a result of the study of the synthesized samples, it is shown that with an increase in the volume of the solution, a decrease in the surface resistance and an increase in the specific conductivity are observed. It is determined that the optimal concentration of the precursor SnCl4•5H2O to achieve the minimum surface resistance of samples coated with SnO2 is 0,25 mol/l.